Analysis of the Causes of Excessive Noise and Vibrations of Live Steam Pipelines - Damian Pietrusiak; Jerzy Czmochowski; Artur Górski; Artur Iluk; Przemysław Moczko; Michał Paduchowicz (Applied Sciences, 2025)
The article discusses the causes of excessive noise and vibrations of a live steam pipeline in a power unit. A scanning laser vibrometer was used to measure the vibrations of the live steam pipeline for two power units. Additionally, the sound (noise) level of the live steam pipeline was measured with an acoustic camera. A discrete model of the pipeline was created, and FEM modal analysis was performed. Based on experimental tests and numerical simulations, the sources of noise were identified. The final conclusions propose methods of eliminating the harmful noise.